Anthropologists in Global Health Experiments. Issue 5 (2nd September 2016) - Hardon, Anita; Pool, Robert
ABSTRACT: Can global health experiments be part of more flexible systems of knowledge generation, where different bodies of knowledge come together to provide understanding not only of the outcomes of new interventions but also of the mechanisms through which they affect people's well-being and health? Building past work in which they tried to transform how global health experiments are carried out and inspired by the articles in this special issue, the authors of this commentary argue that strategic collaboration is needed to break the hegemony of randomized controlled trials in designing global health technologies. More open-ended experiments are possible if anthropologists team up with innovative researchers in biomedicine to develop new conceptual models and to adopt novel observational techniques and 'smart' trials that incorporate ethnography to unravel complex interactions between local biologies, attributes of health systems, social infrastructures, and users' everyday lives.